A Study on Knowledge Gain, Adoption and Attitude towards Training of Farm Women in Port Blair, Andaman - Ahmed, S.K. Zamir; Roy, S. Dam (Indian Journal of Extension Education, 2013)
An Ex Post Facto study was conducted in four clusters of villages in South Andaman block, Port Blair of South Andaman  district. The respondents comprising of 240 farm women who had undergone three days training from KVK-CARI, Port  Blair and also untrained (30 each in both category) on the subjects / enterprises namely mushroom cultivation, kitchen  gardening, layer farming and fresh water pisciculture were randomly selected to infer the knowledge gain, adoption and  the attitude towards the training. The respondents in the trained category gained medium level of knowledge, adoption and  attitude towards training, whereas those of untrained gained low level. Among the total respondents in the trained farm  women category, more than half (63.34%) showed medium level of adoption followed by high (23.33%) and low  (13.33%), whereas in the untrained farm women category a little more than half (50.84%) showed low level of adoption  followed by medium (28.33%) and high (20.83%) in all enterprises. It could be noticed that among the total respondents in  the trained women category, more than half (60.83%) showed medium level of attitude towards training followed by high  (27.50%) and low (11.67%), whereas in the case of untrained farm women a little less than half (48.33%) showed low  level of attitude towards training followed by medium (30.00%) and high (21.67%). The finding will be of immense help  in modifying the training process and regulating the variables to make them effective. It will also help the trainers in  planning and designing the programmes on scientific lines.
Keywords: Knowledge gain; technological adoption; attitude; training; farm women